Trefftz methods for plane piezoelectricity - Sze, K. Y.; Jin, W. G.; Sheng, N.; Li, J. (Computer Assisted Methods in Engineering and Science, 2023)
Starting from the governing equations, the general solution and the complete solution set for plane piezoelectricity are derived in this paper. Subsequently, the Trefftz collocation method (TCM) is formulated. TCM falls into the category of Trefftz indirect methods which adopt the truncated complete solution set as the trial functions. Similar to the boundary element method, the solution procedure of TCM requires only boundary discretization. Numerical examples are presented to illustrate the efficacy of the formulation.